2001
DOI: 10.1159/000059349
|View full text |Cite
|
Sign up to set email alerts
|

A case of azoospermia in a bull carrying a Y-autosome reciprocal translocation

Abstract: During normal cytogenetic investigations on the Chianina cattle (BTA) breed, a normal looking young bull was found to carry an abnormal Y chromosome which was a product of a reciprocal translocation between chromosomes Y and 9. This was revealed by both CBA- and RBG-banding techniques and was clearly confirmed by FISH-mapping analysis with IDVGA50 (which paints the complete Yq arm in a normal Y), as well as with AMD1, CGA, IGF2R (mapping to BTA9q16, BTA9q22 and BTA9q27→q28, respectively) and SRY (mapping to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 5 publications
1
28
0
1
Order By: Relevance
“…Iannuzzi et al [2001a] identified the translocation rcp(1; 5)(q21;q11) in Grey Alpine cattle by means of banding techniques and human painting probes. Using BAC clones, the rcp(Y;9) (q12.3;q21.1) and rcp(11; 22)(q28;q12) translocations were identified in Chianina cattle [Iannuzzi et al, 2001b;Molteni et al, 2007], rcp(9; 11)(q27;q11) in the Marchigiana breed , pericentric inversion of Y chromosome inv(Y)(p11;q12.2) in Podolian cattle [Iannuzzi et al, 2001c] and the pericentric inversion of BTA29 in the Blonde d'Aquitaine cow ( fig. 1 ).…”
Section: Fish Applied To Clinical Cytogenetics Of Domestic Animalsmentioning
confidence: 99%
“…Iannuzzi et al [2001a] identified the translocation rcp(1; 5)(q21;q11) in Grey Alpine cattle by means of banding techniques and human painting probes. Using BAC clones, the rcp(Y;9) (q12.3;q21.1) and rcp(11; 22)(q28;q12) translocations were identified in Chianina cattle [Iannuzzi et al, 2001b;Molteni et al, 2007], rcp(9; 11)(q27;q11) in the Marchigiana breed , pericentric inversion of Y chromosome inv(Y)(p11;q12.2) in Podolian cattle [Iannuzzi et al, 2001c] and the pericentric inversion of BTA29 in the Blonde d'Aquitaine cow ( fig. 1 ).…”
Section: Fish Applied To Clinical Cytogenetics Of Domestic Animalsmentioning
confidence: 99%
“…sence of gamete production (azoospermia), as, for instance, in the case of gonosome-autosome translocations (Iannuzzi et al, 2001;Sun et al, 2005). Carriers of translocations generally produce two types of gametes, either genetically balanced (carrying the rearranged chromosomes or not) or genetically unbalanced with a gain or loss of part of the genetic material (the relative proportions depending on the abnormality involved).…”
mentioning
confidence: 99%
“…Furthermore, several loci were localized on chromosome regions lacking markers (DIK26 to 1q24, CSSM147 to 2p27, McM218 to 4q15, D10S2 to 7q22, D9S5 and D9S3 to 8q14 and 8q24, respectively, OarCP09 and BM4208 to 9q22 and 9q24, respectively, BM0848 to 15q29, D20S10 to 16q13.3, D18S17 and D21S12 to 18q22, ADCY to 23q25, D27S10 to 26q15) (SheepBase; Iannuzzi et al, 1999Iannuzzi et al, , 2000bIannuzzi et al, , 2001aIannuzzi et al, , 2001bDi Meo et al, 2000. More precise localizations of molecular markers and their ordering along the chromosomes are particularly important in order to detect chromosome rearrangements that may have occurred during chromosome evolution of bovids (Piumi et al, 1998;Iannuzzi et al, 2000aIannuzzi et al, , 2001b or chromosome abnormalities, as demonstrated in cattle (Iannuzzi et al, 2001c(Iannuzzi et al, , 2001d. With the 60 loci assigned in the present study, the total number of loci assigned to specific sheep chromosome regions amounts to 211 (SheepBase).…”
Section: Resultsmentioning
confidence: 89%